Continuous frequency and isolation reconfigurable MIMO PIFA antennas using liquid materials. Issue 4 (31st January 2022) - An, Miao; Li, Yao; Zhai, Huiqing; Sun, Qiao
Abstract: In this paper, a continuous frequency and isolation reconfigurable multiple input multiple output (MIMO) PIFA antenna loaded with a decoupled neutralization line structure is proposed. A pair of transparent boxes made of PC material was loaded between the radiation plane and the ground to provide conditions for reconfiguration. The frequency reconfigurable range is from 1.58 GHz to 1.08 GHz (frequency tuning range 37.5%) which is achieved by controlling the height of pure water from 0 mm to 9.15 mm. Pure water in the PC box will interfere with the electric field distribution near the antenna and change the effective dielectric constant of the dielectric. In the range of 1.08 1.58 GHz continuous frequency reconfigurable, the load of neutralization line makes the mutual coupling of working frequency band decreases by at least 8 dB. And the antenna prototype is measured. The simulation results are in good agreement with the measured results, which verifies the feasibility of this technology.